PERUBAHAN KADAR AIR DAN KADAR PATI UBI KAYU (Manihot utilissima) SELAMA PENGERINGAN MENGGUNAKAN ROOM DRYER - Ramadani, Rezky Wahyuni; Yahya, Muhammad; Jamaluddin P, Jamaluddin P (Jurnal Pendidikan Teknologi Pertanian, 2017)
The research aims to know the changes of water content  and starch content of cassava during drying use a room dryer. The research  was conducted by use a completely randomized design (CRD) 5 treatment. Parameters that was observed is water content, starch content and hedonic test to cassava chips that was dried. Data analyzed using analysis variance (ANOVA). The results show that the water content and starch content during drying was changed but tend to stop at six hour of drying totaled 11,68% of the water content and 69,84% of the starch content. For hedonic test, the most preferred chips texture is cassava that dried for four hours.